A participação do trabalhador ferroviário na composição do patrimônio cultural intangível da ferrovia paranaense - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2012)
This work aims to recognize the railway workers still alives in Parana , of the Road of railroad Sao Paulo - Rio Grande do Sul - Paraná trunk as part of the acquis rail intangible assets, seeking to valuethe participation of this category in the history of railroad and the transformation of the territory of Paraná, in the mid-twentieth century. The analysis is based on the conceptual understanding of the territory. The railroad consisted in a transforming element of social relations and spatial of the cities of Paraná during part of the twentieth century, also created a category of workers that has, beyond of a "know-how" specific, memories and historical accounts of life and work.In this study the social memory is used as an instrument of cultural construction and a method of analysis, namely: memory of railroad worker , memories of the railway users and historical memories over the railway and on the cities that emerged and developed the margins of railway line. The study theoretical and conceptual is made through of as territory elements, culture and heritage in order to understand the current setting of heritage cultural railway, as an important social element, besides the analysis of scientific papers by authors from Parana, which directed their attention to different approaches to the railroad. the narratives of the railway workers in Parana are comprovatórios elements of their participation in the history of the railroad, which are complementary to other sources researched,seeking to value the Brazilian railroad worker, presenting similarities that go beyond the clipping region, showing that this category is recognized nationally.
Keywords: Patrimônio cultural ferroviário; formação espacial; território usado; trabalhador ferroviário; memória; Cultural heritage railway; training space; territory used; railroad worker and memory; CNPQ::CIENCIAS HUMANAS::GEOGRAFIA